2018
DOI: 10.21608/ejbo.2017.1793.1125
|View full text |Cite
|
Sign up to set email alerts
|

New Pottiaceae records to the moss flora of Libya

Abstract: P OTTIACEAE includes up to 5,311 species worldwide. It is the largest moss family in Libya with 41 out of a total of 98 species known from this country. Most of the species are quite old records based on collections published before 1932. In this recent work 20 Pottiaceae mosses are reported from Libya including two new records namely; Microbryum rectum (With.) R.H.Zander and Weissia controversa var. crispata (Nees and Hornsch.) Nyholm. Descriptions and illustrations of the two new records together with geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…After careful study of the 19 specimens it was found that 9 of them belong to Bryaceae, while the other 10 belong to four species of Pottiaceae recorded earlier by Ros et al (2013) and Youssef et al (2017b) namely; Barbula convoluta Hedw., Crossidium squamiferum (Viv.) Jur., Didymodon vinealis (Brid.)…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…After careful study of the 19 specimens it was found that 9 of them belong to Bryaceae, while the other 10 belong to four species of Pottiaceae recorded earlier by Ros et al (2013) and Youssef et al (2017b) namely; Barbula convoluta Hedw., Crossidium squamiferum (Viv.) Jur., Didymodon vinealis (Brid.)…”
Section: Resultsmentioning
confidence: 92%
“…It is preceded by two families namely Brachytheciaceae (18 species) (Youssef et al, 2017a) and Pottiaceae (43 species) (Youssef et al, 2017b) and followed by 13 families ranging between 1 -5 species (Ros et al, 2013).…”
Section: Mohr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Map showing sites of old and new collection of mosses in Libya. 1-Tobruk, 2-Darnah, 3-Chersa, 4-Al Qubbah, 5-Mechili, 6-Susa, 7-Shahet, 8-Beida, 9-Wadi Kouf, 10-Mas'sa, 11-Hani;ya, 12-Tocra, 13-Tecniz, 14-Al Marj, 15-Tolmetta 16-Benghazi, 17-Tripoli, 18-Borgo and 19-Gharian, The part that has been, hitherto, published on these recent moss collections confirmed the existence of 25 of the old Libyan moss records (Youssef et al 2017a, b andYoussef 2017) and added 14 new records to the bryoflora of Libya; 1 Fabroniaceae (Shabbara & Ghanem, 2006), 2 Orthotrichacea (Youssef et al 2009a, b), 7 Brachytheciaceae (Youssef et al 2017a), 2 Pottiaceae (Youssef et al 2017b) and 2 Bryaceae (Khalil & Youssef 2017). The 3 species (1 Fabroniaceae and 2 Orthotrichacea) were included in the list of Ros et al (2013) which maintained 91 taxa, while the other 11 species (7 Brachytheciaceae, 2 Pottiaceae and 2 Bryaceae) raised the total number of the mosses known from Libya to 102 taxa.…”
Section: Introductionmentioning
confidence: 79%